Study of the Electrical Conduction Mechanism in Low-Frequency Field for CuMnO2 Crednerite-Type Materials Obtained by Microwave-Assisted Hydrothermal Synthesis - Catalin N. Marin; Maria Poienar; Antoanetta Lungu; Cristian Casut; Paula Sfirloaga; Iosif Malaescu (Crystals, 2025)
The electrical conductivity of nanocrystalline CuMnO2 samples, obtained by microwave-assisted hydrothermal synthesis (MWH), is studied by impedance spectroscopy over a frequency range of 30 Hz to 2 MHz and a temperature range from 30 to 120 °C. Three samples are prepared to start from a mixture of sulphate reactants, at two synthesis temperatures and different reaction times (of applying microwaves): sample S1 at 80 °C for 5 min; sample S2 at 120 °C for 5 min and sample S3 at 120 °C for one hour. The static conductivity values, σDC of samples S2 and S3, are approximately equal but larger than those of sample S1. This result suggests that using MWH synthesis at 120 °C, with different reaction times (samples S2 and S3), is sufficient for microwaves to be applied for at least 5 min to obtain samples with similar electrical properties. The experimental data were analysed based on three theoretical models, demonstrating that the most appropriate theoretical model to explain the electrical conduction mechanism in the samples is Mott’s variable range hopping (VRH) model. Using this model, the activation energy of conduction, (EA,cond), the density of localized states near the Fermi level, N(EF), the hopping distance, Rh(T), the hopping energy, Wh(T) and the charge carrier mobility (μ) were determined for the first time, for microwave-assisted hydrothermally synthesized crednerite. Additionally, the band gap energy (Wm) and hopping frequency (ωh) were evaluated at various temperatures T. Understanding the electrical conduction mechanism in the polycrystalline CuMnO2 materials is important for their use in photo-electrochemical and photocatalytic applications, photovoltaic devices, and, more recently, in environmental protection.